INGLIZ TILI OʻQITISH JARAYONIDA KOLLABORATIV TA’LIM MOHIYATI VA SAMARADORLIKKA ERISHISH YOʻLLARI - Mamataliyeva, X.M. (SCIENCE and SOCIETY, 2025)
This article analyzes the essence and effectiveness of the collaborative learning methodology. During the research, it has studied how changes occur in the process of students’ learning based on interactive approaches. The effectiveness of collaborative education in teaching English was determined and confirmed through statistical analysis. The results show that this method is important in increasing cooperation between students, developing communication skills and improving educational efficiency.